RANCANGAN PROTOTIPE RECEIVER VOR BERBASIS RTL-SDR SEBAGAI ALAT BANTU GROUND INSPECTION - Ilham Destyo Arnito; Achmad Setiyo Prabowo; Totok Warsito; Yuyun Suprapto (Politeknik Penerbangan Surabaya, 2020)
The purpose of designing a VOR Receiver Prototype is to design a receiver that can tell the DVOR transmission parameters received at the Ground Station. From research and design. In its application, the prototype of the VOR Receiver device uses RTL-SDR to process the emission results produced by air navigation equipment that can display information like PIR, one of which is the DVOR. This method used is the application of radio receivers through small hardware with a signal processing block in the form of software in the GNURadio application which is tested through two points as sampling during research observations. The information obtained is in the form of Spectrum, Phase, Azimuth, RF Level, Frequency Error, IDENT. Where the information is shown on a display in the form of numbers, graphics and images like PIR (Portable ILS / VOR Receiver). So that it can be used to assist navigation technicians in Ground Inspection activities.